Ameboma of the colon with amebic liver abscess mimicking metastatic colon cancer - Fernandes Hilda; D′Souza Clement; Swethadri G; Ramesh Naik C (Wolters Kluwer Medknow Publications, 2009)
Amebic colitis is common in developing countries, with its variable and non-specific symptoms. Amebomas occur rarely, resulting from the formation of annular granulation tissue, usually in the cecum and in the ascending colon. This report describes the case of a 59-year-old male who presented with abdominal pain. Radiological examination depicted concentric thickening of the cecal wall with mass formation and a cystic lesion in the liver. The endoscopy performed showed a growth in the ascending colon. Biopsy revealed extensive necrosis and inflammatory cells. The patient was referred to this hospital for surgical treatment with a provisional diagnosis of carcinoma of the colon. Peroperatively, a cecal mass was identified. However, suspected secondaries were not seen on the surface of the liver. Histological examination of the right hemicolectomy specimen revealed cecal and ascending colon amebomas. Trophozoites of Entamoeba histolytica were better recognized after periodic acid-Schiff staining. Treatment with Metronidazole for 2 weeks followed by diloxanide furoate for an additional 2 weeks was administered. The liver lesion resolved completely after 8 weeks. Colonic ameboma accompanied by amebic liver abscess may be misdiagnosed as metastatic colon cancer. A high index of suspicion is essential for diagnosis when dealing with colonic masses and liver lesions, especially in the tropics.